Wybrane aspekty przygotowań Polski do uczestnictwa w europejskim rynku handlu emisją CO₂ - Graczyk, Andrzej (Selected aspects of Poland’s preparations for participation in European CO₂ emission trading market, 2006)
In the first part of the paper the political and legal grounds for the emission rights market in the European Union are presented. The second part discusses the problems concerning the implementation of the market in Poland: the initial allocation of emission rights, potential areas of controversy in setting emission rights quotas. In the final part the author points out the economic benefits of participation in the emission trading system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12), 2006, nr 1122, s. 74-83